Avaliação da imagem corporal de idosas - Biasuz, Priscilla Bastos Mattos (2016)
INTRODUCTION: The construction of a young, slim body image, given as ideal by society, requires some procedures that sometimes become impossible to achieve due to genetic, economic and sociocultural factors of each individual, especially during aging. The aging process is inevitable, but the aspects related to physical activity, and an active lifestyle may contribute with functional independence and better physical looks assessment. OBJECTIVE: To assess the bofy image of independent elderly women. METHODS: 73 women participated the research, average-aged 64,05 ± 4,22 functionally independent and without cognitive compromising indicators. To characterize the elderly women's profiles, a sociodemographic questionnaire was made. For body image assessment, it was used the Body Shape Questionnaire (BSQ) and the Stunkard silhouettes scale. On body composition evaluation, bioimpedance (inbody S10) was applied. For self image perception classification, data were shown in percentages, and a Spearman corelation was made. RESULTS: The elderly women's profile investigated in this study showed they presented independence, mostly married, with elementary school concluded, family income of 2 to 4 minimum wages, retired, did not live alone and had two kids, did not use the Internet and participated the groups for old people and physical exercise. About body image, results showed that 57 (78%) of the elderly women present body insatisfaction by overweight, and 3 (4%) showed dissatisfaction by slenderness and still, only 13 (18%) of the elderly women indicated that they are bodily satisfied. On body distortion, it was observed, by means of results, that 48 (66%) of the elderly women showed absence of disorder; 16 (22%) light disorder; 4 (5%) moderate; 5 (7%) grave disorder. As for correlations, age wasn't meaningful, being extremely meaningful the BMI p < 0,0001, CB p < 0,0001 and CC with p < 0,0004 and very meaningful for % G variable, p < 0,0015. As for correlations related to BSQ, age and CC did not present statistical difference, by means of the respective values: p < 0,1106 and p < 0,3697. Meaningful values were identified in % G variables; BMI; CB; presenting themselves, respectively: p < 0,0372; p < 0,0332; p < 0,0433. Conclusion: The body composition changes brought by aging influence negatively the assessment of body self image of the elderley women investigated.